ARAHAN PENATAAN JALUR PEDESTRIAN KAWASAN NOL KILOMETER KOTA MAKASSAR: Obyek studi Penggal jalan Ahmad Yani, kota Makassar - HASMUNIR, HASMUNIR ([Yogyakarta] : Universitas Gadjah Mada, 2015)
The shifting tendency of Makassar’s recent development towards its eastern and northern city-part has given much impact to the land usage of the city’s Zero Kilometer district. The district is now utilized to accomodate strategic roles which are mainly cored in Govermental functions as well as those in business, commercial and tourism. Related to tourism sector, the rapid growing of the number of tourists and visitors annualy is entirely butressed by its Colonial heritage which among them are the Capitol City building of Makassar, the Fort Rotterdam and the civic cultural center, Societet de Harmony. The research focuses on the Ahmad Yani pedestrian ways system in Makassar’s Zero Kilometer district, acting as the main research variable that covers the physical urban setting, activities, street’s users, and the changing tendency occured. The research method is conducted by primarly performing a quantitative description in order to summarize an urban design guidelines wellsuited to Ahmad Yani area. The research process includes observation phases based on Place Centered Map theory and Time Budget Method, and an independent interview to gather any information related to the users’ needs. Based on the field observation, the Ahmad Yani pedestrian ways is now utilized to accomodate the street vendors and parking activities, causing the accessbility of the local pedestrians as well as the other kinds of street activities becomes much decreased. The unexpected changing over the pedestrian ways’ utilization shows an uneffective and uncomprehensive planning that requires an immediate solution. Re-arrangement of the corridor urban setting could be emerged by eliminating its physical setting and implementing necessary urban elements that guarantee the public convenience and safety. The research results are concluded into one pedestrian ways’ design guidelines with some considerations as the bases, which are the activities types of the street users as well as the interaction between each activities with its physical setting. Therefore, the guidelines could serve as an effective solution which is not only oriented to meet the pedestrians’ needs, but also those of the street vendors and the public parking. The design guidelines is also expected to be the best model suggested and offered to the local authorities, city planner and architects in order to create a more revitalized Ahmad Yani’s corridor that contributes to the betterment of the Makassar’s city environment and its livinghood.